The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.11646/zootaxa.4323.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the confused identity of Frankliniella panamensis (Thysanoptera: Thripidae)

Abstract: Morphological and molecular characters are provided for distinguishing two similar species of Frankliniella that are commonly found by quarantine authorities in international shipments of horticultural produce, particularly from Colombia where panamensis and occidentalis co-exist in greenhouses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
3
2
0
2
Order By: Relevance
“…To account for any potentially species-level genetic difference, using COI barcoding [ 36 , 43 , 44 ], our molecular data indicated that the NL and DE populations were both F. occidentalis . The divergence between them at 1.18% was consistent with intraspecific variation in WFT reported elsewhere typically as 2–3% [ 43 , 45 ], while inter-species divergences of closely related species of the genus Frankliniella and other thrips genera were generally around 10–21% [ 43 , 45 , 46 ], although it can be as low as 4.4% for cryptic species like some of those found in the genus Pseudophilothrips [ 46 ]. Caution about species status was also driven by the evidence building for F. occidentalis as a cryptic species complex, revealing clades for “glasshouse” and “lupin” through COI barcoding [ 36 , 45 ], which exhibit reproductive and developmental differences and cause varying levels of crop damage [ 47 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To account for any potentially species-level genetic difference, using COI barcoding [ 36 , 43 , 44 ], our molecular data indicated that the NL and DE populations were both F. occidentalis . The divergence between them at 1.18% was consistent with intraspecific variation in WFT reported elsewhere typically as 2–3% [ 43 , 45 ], while inter-species divergences of closely related species of the genus Frankliniella and other thrips genera were generally around 10–21% [ 43 , 45 , 46 ], although it can be as low as 4.4% for cryptic species like some of those found in the genus Pseudophilothrips [ 46 ]. Caution about species status was also driven by the evidence building for F. occidentalis as a cryptic species complex, revealing clades for “glasshouse” and “lupin” through COI barcoding [ 36 , 45 ], which exhibit reproductive and developmental differences and cause varying levels of crop damage [ 47 ].…”
Section: Discussionsupporting
confidence: 86%
“…The divergence between them at 1.18% was consistent with intraspecific variation in WFT reported elsewhere typically as 2–3% [ 43 , 45 ], while inter-species divergences of closely related species of the genus Frankliniella and other thrips genera were generally around 10–21% [ 43 , 45 , 46 ], although it can be as low as 4.4% for cryptic species like some of those found in the genus Pseudophilothrips [ 46 ]. Caution about species status was also driven by the evidence building for F. occidentalis as a cryptic species complex, revealing clades for “glasshouse” and “lupin” through COI barcoding [ 36 , 45 ], which exhibit reproductive and developmental differences and cause varying levels of crop damage [ 47 ]. Sub-specific genetic differences, which may or may not have resulted in the observed behavioural responses of these two populations, is nonetheless possible.…”
Section: Discussionsupporting
confidence: 86%
“…3-A). The use of nuclear and mitochondrial markers as an accurate method to infer speciation has been reported previously (Bensch et al 2004;Gunawardana et al 2017), using COI sequences successfully separated F. panamensis from F. occidentalis, which are two morphological similar species; moreover, these authors also found two different clades within their F. occidentalis specimens, which was similar to our results. We need to study and analyse more specimens from the species F. occidentalis, including specimens collected from other plant hosts, as F. occidentalis is considered polyphagous (Lewis 1997).…”
Section: Discussionsupporting
confidence: 91%
“…In that genus, some closely similar species such as panamensis and occidentalis, have been shown to differ in the state of this character (Gunawardana et al 2017). During the present study, a total of 13 species of Stenchaetothrips have been examined, and a group of microtrichia on the upper surface of the hind coxae has been observed in each of these, including spinalis.…”
Section: Comparisonsmentioning
confidence: 86%